Cartel and Rational Choice Institutionalism:The Case of Garlic Commodity Import in Indonesia - Tampubolon, Tonny Timbul; Lele, Gabriel; Kumorotomo, Wahyudi; ., Suripto (KnE Social Sciences, 2022)
The purpose of this research was to examine why the cartel is still growing in Indonesia, through using an institutional political economy analysis approach, namely rational choice institutionalism. This approach was used so as to investigate how institutional rules and arrangements regulate individual actions and how individual actors try to change rules and regulations that cause institutional problems. This study focused on two cases that depicted the interactions of three actors (entrepreneurs, bureaucrats, and politicians) which helped perpetuate the cartel. Findings indicated that actors can be motivated by the rewards and costs incurred for their actions and pursue their interests rationally. Also, according to the results, the import quota policy which aims to protect domestic producers is vulnerable to misuse and corruption due to the lack of transparency in granting quotas to importers. Keywords: cartel, institutionalism, rational choice, Indonesia